Story Korito by Svetomir Arsić Basara ‒ interpretation - Stojkovic, Marijana (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
This work will attempt to interpret the process of psychologization and characterisation of characters of the short story Korito by Svetomir Arsić Basara, a famous artist, academic, sculptor, and writer. The aim is to show how the context influenced the creation of the short story, bearing a distinct biographical dimension. Korito is a story of the real and tough life of the people in the Šar-mountain area—poverty and the struggle for survival in the amazing but ruthless nature of the mountain region. In the souls and consciousness of all the characters of the story, a kind of psychological drama takes place due to the anguish of a torturous and gloomy life in poverty. In the whirlpool of mixed feelings and the struggle for bare necessities, a rift occurs in their souls, especially the souls of children. That rift will endure and shape their maturation, growing up, and creation. Therein lies the motivation for this story.
Keywords: interpretation; psychologization; characterization; existence; Šar-mountain; autobiographical dimension; context; text